The chick optic tectum developmental stages. A dynamic table based on temporal- and spatial-dependent histogenetic changes: A structural, morphometric and immunocytochemical analysis - Rapacioli, Melina (2011)
Development is often described as temporal sequences of developmental stages (DSs). When tables of DS are defined exclusively in the time domain they cannot discriminate histogenetic differences between different positions along a spatial reference axis. We introduce a table of DSs for the developing chick optic tectum (OT) based on time- and space-dependent changes in quantitative morphometric parameters, qualitative histogenetic features and immunocytochemical pattern of several developmentally active molecules (Notch1, Hes5, NeuroD1, β-III-Tubulin, synaptotagmin-I and neurofilament-M). Seven DSs and four transitional stages were defined from ED2 to ED12, when the basic OT cortical organization is established, along a spatial developmental gradient axis extending between a zone of maximal and a zone of minimal development. The table of DSs reveals that DSs do not only progress as a function of time but also display a spatially organized propagation along the developmental gradient axis. The complex and dynamic character of the OT development is documented by the fact that several DSs are simultaneously present at any ED or any embryonic stage. The table of DSs allows interpreting how developmental cell behaviors are temporally and spatially organized and explains how different DSs appear as a function of both time and space. The table of DSs provides a reference system to characterize the OT corticogenesis and to reliably compare observations made in different specimens. © 2011 Wiley-Liss, Inc.